Recovering Australia's arid‐zone ecosystems: learning from continental‐scale rabbit control experiments. Issue 4 (28th September 2021) - Finlayson, Graeme; Taggart, Patrick; Cooke, Brian
Abstract : Introduced rabbits are a continuing threat to native Australian flora and fauna. Three interventions using biological control agents, myxomatosis, European rabbit fleas, and rabbit hemorrhagic disease, have reduced rabbit abundance and kept numbers low over the last 70 years. We considered the benefits of biological control for native fauna to put the role of rabbits in influencing vegetation cover, food supply, and predation into better perspective. Numerous examples exist demonstrating increases in native vegetation and the expansion and recovery of native animal populations at landscape scales following intense rabbit suppression. Ongoing research on methods for supplementing the impact of biological control agents and managing introduced predators are needed to restore Australia's arid‐zone ecosystems. However, many biologists and rangeland managers first need to reevaluate the misconception that removing rabbits also introduces other serious and insurmountable problems such as prey‐switching by introduced cats and foxes.